2003
DOI: 10.1093/brain/awg204
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia in The Netherlands: patient characteristics and prevalence estimates from a population-based study

Abstract: Since 1994, a population-based study of frontotemporal dementia (FTD) in The Netherlands has aimed to ascertain all patients with FTD, and first prevalence estimates based on 74 patients were reported in 1998. Here, we present new prevalence estimates after expansion of our FTD population to 245 patients, with emphasis on the prevalence in the province Zuid-Holland where the main study centre is located. All neurologists and physicians in nursing homes received a yearly postal enquiry about suspected FTD cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
304
6
25

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(351 citation statements)
references
References 28 publications
10
304
6
25
Order By: Relevance
“…Despite several contributions based on small series, the presence of ubiquitin-related pathology within the cerebral cortex is still considered a rare phenomenon in typical FTD cases [2,6,15,18,21,22,24,34,35,40,47,48]. However, a recent population-based study of FTD in Netherlands indicated that 25% of typical FTD cases displayed ubiquitin-positive inclusions [36]. Our data go beyond these findings in that they indicate that the appearance of ubiquitin-positive inclusions and neurites is an age-unrelated phenomenon, which occurs in the majority of typical FTD cases mainly in the dentate gyrus of the hippocampus and to a lesser degree in the temporal and frontal neocortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several contributions based on small series, the presence of ubiquitin-related pathology within the cerebral cortex is still considered a rare phenomenon in typical FTD cases [2,6,15,18,21,22,24,34,35,40,47,48]. However, a recent population-based study of FTD in Netherlands indicated that 25% of typical FTD cases displayed ubiquitin-positive inclusions [36]. Our data go beyond these findings in that they indicate that the appearance of ubiquitin-positive inclusions and neurites is an age-unrelated phenomenon, which occurs in the majority of typical FTD cases mainly in the dentate gyrus of the hippocampus and to a lesser degree in the temporal and frontal neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…This latter form is characterized clinically by the presence of MND with dementia and neuropathologically by the formation of ubiquitin-positive and tau-negative intraneuronal inclusions in hippocampus and subcortical structures [3,7,9,11,27,31,42,46]. However, ubiquitin-positive intraneuronal inclusions and dendrites have also been reported in familial [6,20,24,35] and in a few sporadic FTD cases in the absence of MND [2,15,18,21,22,36,40,47,48] as well as in FTDP-17 cases [17,28,35]. These observations question the specificity of ubiquitin-positive inclusions and their clinical relevance in the context of FTD.…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated prevalence of 15/100,000 in the age group of 45–64 years, FTLD represents a significant challenge for social welfare 1, 3. FTLD can present with a variety of syndromes, including progressive supranuclear palsy, corticobasal degeneration, and progressive aphasia, but the most common presentation is progressive change in personality with abnormalities in socioemotional behavior, referred to as the behavioral variant of frontotemporal dementia (bvFTD) 4.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 50% of FTD patients have a positive family history of dementia, mainly with autosomal dominant inheritance [Chow et al, 1999;Poorkaj et al, 2001;Rosso et al, 2003]. The majority of FTD families have been linked to chromosome 17q21.…”
Section: Introductionmentioning
confidence: 99%